Fetal and perinatal outcome associated with small cerebellar diameter based on second‐ or third‐trimester ultrasonography. (29th May 2019) - Atallah, Anthony; Guibaud, Laurent; Gaucherand, Pascal; Massardier, Jerome; des Portes, Vincent; Massoud, Mona
Abstract: Objective: To examine the outcome of pregnancy with fetal transverse cerebellar diameter (TCD) below the fifth percentile based on routine second‐ or third‐trimester ultrasonography. Methods: We retrospectively analyzed the outcomes of 12 344 women according to TCD Z scores based on systematic second‐ or third‐trimester ultrasound examination between 2007 and 2015. Information on major malformations, chromosomal anomalies, intrauterine or neonatal demise, and other abnormal findings were collected. Results: In total, 408 fetuses with small prenatal TCD underwent clinical investigation; 160 major malformations were noted, consisting mainly of neurological or cardiac anomalies (39, 2%%). Chromosomal anomalies were reported in 39 (9.5%) and intrauterine or neonatal demise in 41 cases (10%). Major malformations and chromosomal anomalies were found in 46.4% and 10% of fetuses with extremely small TCD ( Z score < −2.5), respectively, 31.3% and 12.7% of fetuses with small TCD ( Z score between −2.0 and −1.645), and 39.6 % and 7.7% of fetuses with subnormal TCD ( Z score between −2.0 and −1.645). Intrauterine or neonatal demise was noted in 22%, 8.8%, and 4.8% of fetuses with extremely small, small, and subnormal TCD, respectively ( P < .05). Among intrauterine growth‐restricted fetuses, fetal demise or neonatal adverse outcome was reported in 75%, 81.8%, and 18.5%, respectively. Of all the fetuses, 2.2% were lost to follow‐up. Conclusion: A small cerebellar diameter below the fifth percentile is a relevant marker to detect associated anomalies during routine ultrasound examination in the second or third trimester. This is related to a high rate of fetal malformations, chromosomal anomalies, and genetic disorders, regardless of the severity of the cerebellar small size. Small TCD seems to be a prognostic factor for fetal growth restriction. Therefore, when facing a TCD below the fifth percentile, patients should be referred for further sonography and fetal karyotyping. Abstract : What's already known about this topic? Easy and reproducible measure of the transverse cerebellar diameter (TCD) is a gateway to several, potentially severe, fetal anomalies. TCD is not currently included among the recommended sonographic fetal biometric measurements of basic scan. What does this study add? A threshold of TCD below the fifth percentile identifies fetuses at high risk for chromosome anomalies, major structural anomalies, and adverse outcome. Among growth‐restricted fetuses, a TCD Z score below −2 is highly associated with fetal demise or adverse neonatal outcome. TCD should be part of the standard fetal biometric parameters measured at routine (basic) scan.